MENGURAI PERMASALAHAN DISTRIBUSI ZAKAT KEPADA FAKIR MISKIN: PENGALAMAN ORGANISASI PENGELOLA ZAKAT BAZNAZ, DOMPET DHUAFA, DAN LAZIZMU - Fiqih Afriadi; Yulizar D Sanrego (Jurnal Madania)
The Problems Solving of Zakah Distribution for the needy Persons: the Experiences of Baznaz Management, Dhuafa Finance, and Lazizmu. This paper tries to unravel the problems of distribution of zakah through clustering problems by using problem decomposition Analytic Network Process (ANP) method. Decomposition of the problem is done with the study of literature and indepth interviews with experts and practitioners who have in-depth knowledge and extensive experience in the world of zakah. This study also conducted a comparative analysis of priority of the various problems and its possible solutions. The results of this study indicate that some of the problems to be used as a main priority are; the lack of standards in the determination mustahik priority, yet the landscape and the data base mustahiq, mental problems and less of mustahik awareness and overlap distribution with government programs. While the two solutions as the top priority to be done ie; the establishment of a data base mustahiq, and cooperation, synergy and coordination between OPZ with the government, as well as with various of other institutions